Puerperal care practices developed by nurses in the Family Health Strategies - Críslen Malavolta Castiglioni; Luiza Cremonese; Lisie Alende Prates; Maria Denise Schimith; Graciela Dutra Sehnem; Laís Antunes Wilhelm (Universidade Federal de Santa Maria, 2020)
Objective: to know the care practices developed by nurses from the Family Health Strategies for women in the puerperium. Method: qualitative research conducted between December 2016 and January 2017 through interviews with nine nurses. The data were analyzed according to the operative proposal. Results: The puerperal appointments occur around one to two times within 30 days and are performed mostly by nurses through obstetric physical examination, care with the cesarean or episiotomy incision, evaluation of emotional aspects and guidelines on sexuality, reproductive planning, breastfeeding, newborn care and the bond between mother and baby. Conclusion: the nurses perceive the relevance of the care practices and their main characteristics, because they recognize the hormonal, emotional and social changes of the period and the importance of the work of professionals in this stage surrounded by changes, adaptations and vulnerability.